Analysis of Medication Compliance of Hypertension Patients of Productive Age in the Prolanis Group - Dariya; Arie Wahyudi; Muhammad Prima Cakra Randana (Jurnal Vokasi Kesehatan, 2026)
Hypertension is a degenerative disease that requires long-term management because non-compliance in taking antihypertensive medication can trigger fatal cardiovascular complications. This study aims to analyze the level of medication adherence in productive-age hypertensive patients (15-64 years) who are members of the PROLANIS group at the Muara Telang Community Health Center, and to identify the factors that influence it. This type of research is quantitative observational analytic with a cross-sectional approach. The study sample consisted of 76 respondents selected using a purposive sampling technique. Data collection was carried out using the Morisky Medication Adherence Scale (MMAS-8) questionnaire and the Brief Illness Perception Questionnaire (B-IPQ). Data analysis used the Chi-square test (α = 0.05). The results of univariate analysis showed that the majority of respondents were compliant with taking medication, namely 48 people (63.2%), while 28 people (36.8%) were non-compliant. Bivariate analysis results showed no association between age (p=0.892) and gender (p=1.000) with adherence. Conversely, there was a significant association between education (p=0.028), disease perception (p=0.007), and income (p=0.003) with adherence. Health education regarding hypertension as a chronic disease, the importance of adherence to antihypertensive medication, and the prevention of complications needs to be carried out continuously